عزل وتحديد الفطريات المحمولة على بذور صنفين من فول الصويا [ Glycine max (L.)Merril ] وتأثير نسبة الإصابة في إنبات البذور. - يازجي ميساء (Latakia University Journal -Biological Sciences Series, 2014)
هدفت الدراسة إلى عزل وتحديد الفطريات المحمولة على بذور صنفين من فول الصويا، Sb172 وSb44 باستخدام طريقة أوراق النشاف المبللة وطريقة أطباق البتري الحاوية وسط P.D.A. تم تحديد 21 نوعاً تنتمي إلى 10 أجناس، منها الرميّ ومنها الطفيليّ. بينت طريقة أطباق الـ P.D.A العدد الأكبر من الفطريات مقارنة بالطريقة الأخرى، وكان الفطر Aspergillus أكثر الأجناس تردداً بنسبة 44.20% للصنف Sb172 و45.14% للصنف Sb44، يتبعه الفطر Cladosporium، ثم Fusarium في حين بيّن الجنس Colletotrichum أقل نسبة تردد (0.85%) عند الصنف Sb172. اختلفت النسب المئوية لإنبات وإصابة البذور بين الصنفين، وكانت نسبة إنبات بذور الصنف Sb172 أعلى من الصنف Sb44 بكلتا طريقتي الزراعة، وبلغت 94% للأول و92% للثاني بطريقة أوراق النشاف المبللة، في حين كانت النسبة 52% و34% للصنفين على الترتيب بطريقة أطباق P.D.A، لكن نسب الإصابة كانت بشكل عام لدى الصنف الأول أدنى من الثاني وذلك بكلتا الطريقتين. أظهرت النتائج أن البذور التي كانت نسبة إصابتها أكبر بيّنت نسبة إنبات أقل. The aime of this study was to isolate and identify the seed borne fungi of two varieties of Soybean, Sb172 and Sb44, using blotter method and P.D.A plate method. 21 species belong 10 genus were determined, saprophyte and pathogen Fungi. P.D.A plate method showed the highest number of fungi in comparison with the other method, and the fungus Aspergillus was the most frequent genus with a ratio of 44.2% for the variety sb172 and 45.14% for the variety sb44, followed by the fungus Cladosporium and then Fusarium, whereas the genus Colletotrichum showed the lowest frequent ratio (0.85%) with the variety Sb172. The percentages of seeds germination and infection were differed between the two varieties, and the ratio seeds germination of variety sb172 were higher than the variety sb44 with the both methods of culture, and were equal 94% with prim variety and 92% with the second ones by blotter method, whereas the ratio were 52% and 34% for both varieties respectively by P.D.A plate method. However, the ratio of infection were, in general, lower with prim variety than the second ones by the both method. The results showed the seeds which were highest ratio infection appeared low ratio germination .